Assessing Venturia inaequalis Response to Common Fungicides in Morocco - Safae Gouit; Safae Chiadmi; Khadija Goura; Ikram Legrifi; Moussa El Jarroudi; Zineb Belabess; Abdessalem Tahiri; Abderrahim Lazraq; Mohammed Baala; Rachid Lahlali (Journal of Fungi)
Apple scab, caused by Venturia inaequalis, remains a major challenge for apple production in Morocco, where disease management heavily depends on fungicide applications. However, increasing reports of resistance have raised concerns about the long-term efficacy of commonly used products and the economic sustainability of apple orchards. In this study, we evaluated the sensitivity of five V. inaequalis isolates from the Fes-Meknes region, a key apple-producing area in Morocco, to three fungicides: difenoconazole, trifloxystrobin, and thiophanate-methyl. The identity of the isolates was confirmed based on both morphological characteristics and by molecular analysis of the ITS region. In vitro and in vivo assays revealed significant differences in isolate responses. Difenoconazole consistently showed the highest efficacy, with EC50 values ranging from 0.05 to 1.46 µg/mL, and preventive applications reducing disease severity by up to 85.8% at 10 µg/mL. In contrast, trifloxystrobin and thiophanate-methyl exhibited much higher EC50 values (2.94–29.62 µg/mL and 14.84–1237.20 µg/mL, respectively), indicating widespread resistance, particularly to thiophanate-methyl, whose curative and preventive efficacy rarely exceeded 44%. Preventive treatments were significantly more effective than curative applications for all fungicides tested. These findings highlight the urgent need to revise apple scab management strategies in Morocco, including the rotation of fungicides with different modes of action and the integration of non-chemical approaches. Broader sensitivity monitoring and the use of molecular diagnostics are recommended to better inform sustainable disease control programs.